Non-nompliance terhadap Konvensi Ilo Oleh Pemerintah Yordania: Studi Kasus Pekerja Anak Pengungsi Suriah - Cindana Ekki Prativi; Ika Riswanti Putranti; Andi Akhmad Basith Dir (Journal of International Relations Diponegoro, 2018)
Jordan is a host country for Syrian refugees despite the fact that they have not ratified the1951 Refugee Convention. The high cost of living and the difficulty of obtaininglegitimate employment in Jordan encouraging of child labor cases from Syrian refugeeswho are vulnerable to exploitation. In this case, Jordan has actually ratified the ILOConvention on child labor, but there are still many illegal displaced child laborers. Thisstudy aims to describe the attitude of non-compliance Jordan in adopting ILO convention.In this study, the authors use the concept of non-compliance of the theory of theinternational regime to explain that the state is not always willing to comply withinternational instruments that have been agreed. The research method used is qualitativewhich is done by collecting and analysing data, to find out the reason behind Jordaniannon-compliance even though the government has ratified ILO Conventions. In this study,factors that resulted in the attitude of non-compliance of Jordan, such as the ambiguity ofthe interpretation of the ILO's Conventions by the Jordanian government, the limitedcapability of the state, and the influence of the temporal dimension in the country.